Inter-Religious Tolerance in Indonesia From the Perspective of Pancasila Philosophy - Aufa Fitria; M. Ikhsan Tanggok (Al-Albab, 2020)
Creating peace between religions by building tolerance is required to avoid intolerance. This is one of the ways to respect differences between religions. Indonesia is a multi-ethnic cultural and religious country. Therefore, building tolerance is a must to achieve healthy inter-religious peace as part of the implementation of the Pancasila values. This article aims to explore and keep a record of the perceptions of religious followers, as well as how they are applied in their daily life, especially concerning religious diversity. The ethnographic approach is a method or analysis used to explore and understand information obtained from in-depth individual interviews with religious and community leaders. The findings in this study show that building inter-religious tolerance, especially in Indonesia with its diversity of ethnic groups, cultures, languages, etc., is not easy, but the philosophical values of Pancasila are able to unite them harmoniously and there is no disagreement between religions, which can be seen from the dynamics of community life in Pondok Cabe, Pamulang, with the diversity of religions (Islam, Christianity, and Catholicism). In this place, different religious adherents can interact appropriately and harmoniously. Strengthening the values of Pancasila in building inter-religious tolerance needs to be carried out and promoted. This is one of the suggestions from this study.